2017
DOI: 10.1016/j.rssm.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational transmission of educational attainment in adoptive families in the Netherlands

Abstract: To improve our understanding of the mechanisms underlying the strong association between family background and children's educational attainment, we examined intergenerational transmission within families where genetic transmission is absent. Specifically, we investigated the effect of parent's education and income on the educational attainment of their foreign-born adopted children. A large-scale register database was used, which contains information on the adoption status, educational level in secondary scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
(50 reference statements)
3
6
0
5
Order By: Relevance
“…The genetic nurturing effect on offspring educational attainment has been replicated in several samples 15 , 75 , 78 , 84 86 , 88 , 89 , and a few studies reported that the observed effect was partly explained by family socioeconomic status 14 , 15 , 89 . This finding is compatible with an adoption study which found that adoptive parents with higher income had offspring with increased educational attainment 90 . Other studies reported additional mediating effects of parental IQ 88 , maternal health during pregnancy 89 and parenting behaviours 78 .…”
Section: Resultssupporting
confidence: 90%
“…The genetic nurturing effect on offspring educational attainment has been replicated in several samples 15 , 75 , 78 , 84 86 , 88 , 89 , and a few studies reported that the observed effect was partly explained by family socioeconomic status 14 , 15 , 89 . This finding is compatible with an adoption study which found that adoptive parents with higher income had offspring with increased educational attainment 90 . Other studies reported additional mediating effects of parental IQ 88 , maternal health during pregnancy 89 and parenting behaviours 78 .…”
Section: Resultssupporting
confidence: 90%
“…This is consistent with much of the adoption research to date (e.g. van Vorria et al, 2015;Scheeren et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…This is consistent with much of the adoption research to date (e.g. van IJzendoorn, Juffer and Poelhuis, 2005;Scheeren, Das and Liefbroer, 2017;Vorria, Ntouma and Rutter, 2015).…”
Section: European Studiessupporting
confidence: 88%
“…In addition, SES was indexed by household income. Educational level, which is another common SES indicator, might have yielded different results (for different effects of income and educational level, see, e.g., Scheeren, Das, & Liefbroer, 2017;White, 1982).…”
Section: Discussionmentioning
confidence: 99%